Experimental Investigation on Isothermal Sections at 1273 and 1473 K in the Co–Ti–W System - Shi, Yu; Guo, Cuiping; Li, Changrong; Du, Zhenmin; Hu, Die (Frontiers in Materials, 2022)
The microstructures of 25 annealed alloys and XRD patterns of partial critical alloys in the Co–Ti–W system were investigated by using scanning electron microscopy (SEM) with energy dispersive spectrometer (EDS) and X-ray diffraction (XRD) methods. The isothermal sections at 1273 and 1473 K of the Co–Ti–W system were established. 5 three-phase regions and 5 two-phase regions at 1273 K and 8 three-phase regions and 2 two-phase regions at 1473 K were experimentally determined. The maximum solubilities of W in Co3Ti, αCo2Ti, βCo2Ti and CoTi were determined to be 7. 9 at.%, 1.5 at.%, 5.9 at.% and 1.8 at.% at 1273 K, respectively. The maximum solubilities of Ti in Co7W6 and Co3W were determined to be 11.9 at.% and 15.2 at.% at 1273 K, respectively. The compound Co3Ti with L12 crystal structure was found to be stable at 1473 K in the Co–Ti–W system owing to the addition of W element, which confirmed that W can improve the stability of γ′ with L12 crystal structure in the Co-based superalloys. The composition range of W in Co3Ti was measured to be 7.4–10.4 at.% at 1473 K. In addition, the maximum solubilities of Ti in Co7W6 and W in βCo2Ti and CoTi were 15.4 at.%, 7.6 at.% and 3.1 at.% at 1473 K, respectively. No ternary compounds were found in the Co–Ti–W system at 1273 and 1473 K.